2020
DOI: 10.1111/petr.13812
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the first 6 years of pediatric kidney transplantation in Indonesia: A multicenter retrospective study

Abstract: Background: Pediatric kidney transplantation was only introduced in Indonesia in 2013. We therefore aimed to assess the characteristics and outcomes of transplants performed from its inception to January 2019. Method: The study had a dual-center retrospective design. We examined the records of kidney transplant recipients and then calculated patient and graft survival rates by Kaplan-Meier survival analysis with 95% confidence intervals (95% CI). Results: In total, 12 kidney transplantations were performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Moreover, KRT utilization has increased, particularly for KT. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 However, it remains uncertain whether similar patterns and outcomes have been achieved among the pediatric population, given that the etiologies of kidney failure in children are notably different from those in adults. 5 , 12 , 13 , 14 , 15 , 16 , 17 Since the 1980s, improved patient care and KRT policies have resulted in the acceptance of more challenging patients into pediatric KRT programs, including very young patients, and prioritization of pediatric patients with kidney failure as KT recipients.…”
mentioning
confidence: 99%
“…Moreover, KRT utilization has increased, particularly for KT. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 However, it remains uncertain whether similar patterns and outcomes have been achieved among the pediatric population, given that the etiologies of kidney failure in children are notably different from those in adults. 5 , 12 , 13 , 14 , 15 , 16 , 17 Since the 1980s, improved patient care and KRT policies have resulted in the acceptance of more challenging patients into pediatric KRT programs, including very young patients, and prioritization of pediatric patients with kidney failure as KT recipients.…”
mentioning
confidence: 99%
“…A recently published study from the pediatric kidney transplantation centers in Indonesia reported that all patients had hypertension and 42% of patients had cardiomyopathy before the kidney transplantation and the longest dialysis duration before the transplantation was 72 months. 14 About 86.05% of patients in our study had LVH with eccentric type. The eccentric LVH shows the addition of serial cardiac sarcomere and is associated with volume overload, causing thickening of the cardiac wall and enlargement of the left ventricular space.…”
Section: Discussionmentioning
confidence: 64%
“…Consistent with data from the largest epidermolysis bullosa (EB) registry [6], most reported cases progressed to kidney failure or death within 5 years of IgAN diagnosis. In contrast, only 5% of pediatric IgAN cases required kidney transplantation initially, and 20-25% of children with primary IgAN progressed to kidney failure within 20-30 years post-diagnosis [7][8][9]. Consequently, early detection and appropriate treatment of IgAN are crucial for RDEB patients [6].…”
Section: Introductionmentioning
confidence: 99%